Investigating slant curves within Lorentzian doubly warped product manifolds. - Ayman Elsharkawy; Hoda Elsayied; Abdelrhman Tawfiq; Fatimah Alghamdi (PLoS ONE)
This study investigates the application of Robertson-Walker space in the analysis of slant curves. The study classifies all slant curves and calculates their curvature and torsion. The research shows that slant curves can be analyzed using Robertson-Walker space. The study also finds that doubly warped product manifolds have been more extensively studied than other types of manifolds, including warped product manifold and Minkowski space. These results contribute to our understanding of the use of mathematical structures in the analysis of slant curves and provide a foundation for future research.